Cross‐cultural translation and validation of the Chinese version Distress Tolerance Scale for adolescents with chronic physical disease - Lee, Shu‐Li; Wu, Li‐Min; Lin, Shu‐Yuan; Chen, Tzu‐Han; Lin, Wei‐Ting (Child : care, health & development, 2024)
Introduction Chronic physical disease (CPD) makes life filled with many negative events in adolescents, but not all adolescents experiencing negative life events proceed to develop emotional distress, only those with low emotional distress tolerance (EDT). A valid and reliable scale to measure EDT in CPD adolescents is important for caring for their emotional distress. Therefore, the purpose of this study is to translate the 15‐item English version Distress Tolerance Scale (DTS) into a Chinese version and then validate the scale for measuring EDT of adolescents with CPD. Methods The 15‐item English version DTS was translated into a Chinese version using the translation guidelines for cross‐cultural research. Two cohorts of adolescents with CPD were recruited from four hospitals in southern Taiwan, with the first cohort including 124 adolescents with CPD employed to conduct exploratory factor analysis, corrected item‐total correlation and reliability testing, while the second cohort, consisting of 238 adolescents with CPD, was utilized to examine confirmatory factor analysis and concurrent validity. Results The two‐factor nine‐item Chinese version DTS for Adolescents with CPD (C‐DTS‐A) was developed. Lower scores of the C‐DTS‐A were significantly associated with higher diabetes distress, poorer self‐management, and worse glycaemic control; their correlation coefficients sequentially were −.40, .17 and −.23. Cronbach's α and the test–retest reliability of the two‐factor C‐DTS‐A ranged from .81 to .87 and from .79 to .89, respectively. Conclusion The two‐factor nine‐item C‐DTS‐A with good cross‐cultural translation quality was a reliable and valid scale to assess EDT for adolescents with CPD.